Apigenin suppresses osteoarthritis progression by inhibiting pyroptosis via SIRT1/mTOR pathway-mediated mitophagy - Jiahao Ying; Shijie Li; Anna Ying; Yindong Ding; Xiaoyin Zhu; Jiahao Lin; Kehe Yu (Journal of Functional Foods)
Exploring the therapeutic effects and underlying mechanisms of Apigenin (Api) in managing osteoarthritis (OA) was the primary focus of this research. In this research, X-ray and Safranin-O staining were employed to evaluate the imageology and histomorphology differences in the knee joints of mice in vivo. Techniques such as Western blot analysis, Enzyme-linked Immunosorbent Assay (ELISA), and immunofluorescence staining were applied to examine protein level changes in vitro experiments. In vitro assays indicated that Api significantly reduces the levels of pro-inflammatory mediators and prevents the degradation of the ECM. By promoting SIRT1/mTOR pathway-mediated mitophagy, Api shields chondrocytes from pyroptosis. Further, animal studies demonstrated that Api effectively alleviates the progression of OA by enhancing mitophagy, inhibiting chondrocyte pyroptosis and ECM degradation. Consequently, Api is recognized as an effective and promising therapeutic candidate for the management and treatment of OA.